Chapter Eat to remember. Gastronomical reconfigurations of hunger and imprisonment in contemporary Chinese literature - De Marchi, Serena (Studi e saggi, 2021)
During the famine that befell China following the disaster of the Great Leap Forward, hunger was a major affliction for the individuals undergoing reform in the labor camps. Food - in terms of procurement, consumption, or just discursive recollection - was a central issue in the prisoners' lives and, as a consequence, descriptions of meals and eating practices are a recurring presence in modern Chinese literary texts that revolve around carceral experiences. This contribution investigates three literary works that reconstruct personal experiences of imprisonment by way of eating: Wang Ruowang's Hunger Trilogy (1980), Zhang Xianliang's Mimosa (1984), and Yang Xianhui's Chronicles of Jiabiangou (2003). In these texts, food becomes a privileged perspective through which look at how personal and collective memories are re-appropriated and re-elaborated, as well as to analyze how narratives of the past are consumed and produced.